Pregnancy Outcome After Preterm Rupture of the Membranes Before or After 34 Weeks’ Gestation in a Private Tertiary Referral Hospital - Derbent, Aysel; Simavlı, Serap; İnegöl Gümüş, İlknur and İltemur Duvan, Candan and Kafalı, Hasan and Tatlı, Mansur and Öztürk Turhan, Nilgün (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: To investigate the outcome of premature rupture of the membranes (PROM) before and after 34’weeks of gestation. STUDY DESIGN: A retrospective study, including 85 women with PPROM and 249 women with PROM during the years 2007-2010, was conducted. Data were analyzed using the chi-squared test, the Mann-Whitney test, and Spearman’s correlation analysis. RESULTS: Whereas, twin pregnancy was linked to the occurrence of PROM before 34 week, GDM and/or polyhydramnios were seen in the etiology after 34 weeks’ The latency period between PROM and delivery of the fetus was significantly longer before 34 weeks’ gestation (p<0.001). Admission to the NICU and length of stay were found to be higher in the newborns from this group (p<0.001). They were also associated higher infectious neonatal problems, such as sepsis and pneumonia compared to 34-37 weeks subgroup (p<0.001). CONCLUSIONS: PPROM before 34 weeks had a longer latency, and led to more infectious morbidity and mortality in newborns.